School of Communication’s Graduate Critical Studies Conference - Ackerley, Christine Rose (Stream: Interdisciplinary Journal of Communication, 2016)
School of Communication’s annual Graduate Critical Studies Conference will take place this Friday, April 29th and Saturday, April 30th at Harbour Centre, Room 2945. The theme this year is "Dialectics of Space: Enclosure and Resistance." The Keynote Lecture will be by David McNally: “Spatial Dialectics: Capital, Enclosure, Emancipation” (Friday April 29th, 2:00-3:15pm, Harbour Centre 2945) To reserve your ticket, register here: https://www.eventbrite.ca/myevent?eid=24942163683 There will also be a Public Lecture by Maurizio Lazzarato, titled “Financialization and War: Race, Class, Gender and Subjectivity” on Friday April 29th, 7:00-9:00pm, Harbour Centre 1800. Faculty, staff, graduate students, undergraduate students, and members of the general public are all encouraged to attend. For more details, please see the program attached.